Pengaruh Karakteristik Lalu Lintas terhadap Kondisi Perkerasan Jalan Menggunakan IRI dan SDI - Subhan Mulyana; Eko Walujodjati; Salma Fauzyah (Institut Teknologi Garut, 2025)
Population growth and increased economic activity have led to higher traffic volumes on roads, including on Jalan Limbangan–Leuwigoong in Garut Regency. This condition puts excessive pressure on flexible pavements, causing damage, reducing driving comfort, and increasing maintenance costs. This study aims to analyze the effect of vehicle volume and speed on road conditions using the International Roughness Index (IRI) and Surface Distress Index (SDI) indicators. Data were collected through traffic surveys, speed measurements, the RoadLab Pro application for IRI, and visual surveys based on Bina Marga guidelines for SDI. Simple linear regression analysis was used after classical assumption tests were not met in multiple regression. The results showed that vehicle volume and speed did not significantly affect IRI. Conversely, both had a significant effect on SDI, with a strong relationship: volume (R = 0.740; R² = 54.8%) and speed (R = 0.759; R² = 57.5%). This study confirms that traffic characteristics have a greater effect on road surface damage (SDI) than road roughness (IRI).